A New Theoretical and Methodological Look at Gender Differences in Mathematics Tests: Reasoning, Psychosocial Attitudes, and Multilevel Models - Montero-Rojas, Eiliana (2021)
Acknowledging that gender, as a construct, is an expression of a power structure, observed differences favoring males were explained for two standardized tests of mathematical context: the Mathematics section of the University of Costa Rica’s Admission Test and the Mathematics test from the Secondary School’s Exit Exam. The sample was 487 students in the last year of high school in ten public schools from the Greater Metropolitan Area of Costa Rica; 269 were women. Multilevel regression models were estimated using the scores in these tests as dependent variables. The reduced model only included sex as a predictor, whereas the complete model included, additionally, an indicator of reasoning abilities and the following scales: hostile sexism, benevolent sexism, attitude toward gender equity in mathematics, and self-efficacy in mathematics. Results point out that gender differences are reduced by controlling for reasoning abilities. Benevolent sexism predicted performance in the tests to a lesser degree. There was also evidence of the moderating effect of the school for the relationship between sex and the score in the admission test, and, especially, for the means in the secondary school exit test. Mathematics self-efficacy also had considerable predictive power in the latter. These findings provide evidence of the need for teachers to actively promote self-efficacy in their students, especially women. The considerable differences in the average scores of the Secondary School’s Exit Exam, even though they are all public and from the Greater Metropolitan Area of Costa Rica, suggests the presence of inequities that should be studied more in-depth, including schools beyond this area, which could reveal even more disadvantages.